Mindfulness Based Intervention to Overcome Anxiety in Adolescents - Made Cynthia Agrita Putri Rizwari; Cut Nurul Kemala (Analitika: Jurnal Magister Psikologi UMA, 2022)
Adolescents are prone to show symptoms of anxiety when dealing with school-related matters, such as exams, assignments, choosing university major, and friendships. The transition from online to offline learning as COVID-19 pandemic situation eased off appeared to trigger anxiety in adolescents. This research used repeated-measure design that aimed to examine the effectiveness of a mindfulness-based intervention (MBI) in decreasing the anxiety symptoms of six high school students aged 16-18 years (M = 16,83 years) who reported low-to-moderate levels of anxiety, as well as to improve their mindfulness skills and explore qualitative changes in daily lives after MBI. Quantitatively, after MBI, there was a decrease in anxiety symptoms at 2-weeks and 1-month follow-ups; however, there were no changes in mindfulness skills. Results showed that, after MBI, participants reported more awareness toward bodily sensations and environment, better identification of the source, level, and physical symptoms of anxiety, and more knowledge on how to deal with their anxiety. Through this study, it was found that MBI could reduce adolescents' anxiety symptoms two weeks to four weeks after the intervention was given.